Interworking between WiMAX and UMTS to provide seamless services - Khan, M.M.A.; Ismail, M.F.B.; Dimyati, Kaharudin (Academic Journals, 2010)
This article represents an interworking architecture between Universal Mobile Telecommunications System (UMTS) and WiMAX where Third Generation Partnership Project (3GPP) IP Multimedia Subsystem (IMS) and Mobile IPv4 are applied together to maintain the continuity of an on-going session and for that to keep the Internet Protocol (IP) address to be static while the consumer having internet and data access is roaming in a heterogeneous networking environment of different Radio Access Technologies. The uniqueness of this architecture is that the user mobile device would have multiple transceivers along with intelligence of making decisions of handover. The proposed device would be capable of monitoring the signal strength and processing the packets received from different networks simultaneously. The article abrogates by narrating the potential advantages of the proposed approach to eliminate the packet loss due to handover.